Endothelial function as predictor in patients with coronary syndrome treated by percutaneous coronary intervention. Issue 5 (17th October 2018) - Cheng, Xiaofeng; He, Yun; Fan, Huaping; Liu, Ting; Pan, Wenxu; Wang, Ke; Jin, Jun
Abstract : We aimed at identifying the predictive role of endothelial function assessed by the RH-PAT index (RHI) for future major cardiovascular events (MACEs) in acute coronary syndrome (ACS) patients treated with percutaneous coronary intervention (PCI). We measured RHI in 308 subjects with ACS, and they were divided into the normal endothelial function (NEF) group and the endothelial dysfunction (DEF) group according to the RHI. The subjects were followed up for a mean of 16 months (interquartile range [IQR]: 14–20 months) after PCI treatment, and their MACEs were also recorded. Cumulative incidence curves were constructed for time-to-event variables with Kaplan–Meier estimates and compared using the log-rank test. The overall incidence of MACEs was 25.39% in the DEF group and 15.96% in the NEF group ( P <0.05). Kaplan–Meier analysis also demonstrated a significantly higher probability of MACEs in the DEF group than in the NEF group (log-rank test: P <0.05). Multivariate Cox hazard analysis identified RHI (Model 2, adjusted by blood pressure, hazard ratio [HR]: 0.425; 95% confidence interval [CI]: 0.198–0.914; P =0.029) and SYNTAX score (HR: 1.043; 95% CI: 1.019–1.067; P <0.001) as independent predictors of future MACEs after PCI treatment in ACS patients. Endothelial function measured by reactive hyperemia-peripheral arterial tonometry (RH-PAT) is impaired in ACS subjects treated with PCI. The RHI was an independent predictor of MACEs, suggesting that RHI may be useful as a candidate biomarker in the risk stratification of patients with ACS after PCI treatment.